2018
DOI: 10.1097/jcn.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Korean Americans

Abstract: Data on subgroups of Asian Americans indicate that Korean Americans have significant lifestyle-related cardiovascular disease risks, which could be a critical agenda for researchers and clinicians to better understand cardiovascular health disparities in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…To date, epidemiological evidence of cardiovascular disease (CVD) prevalence specific to KAs is scarce. Furthermore, recent research suggests that there are considerable differences in CVD risk factors among KAs compared to non-Hispanic Whites (Shin et al, 2018). According to the 2011-2017 California Health Interview Survey (CHIS) with adults ages 18 years or older, one in four KA adults (24.3%) had high blood pressure (Adia et al, 2020).…”
mentioning
confidence: 99%
“…To date, epidemiological evidence of cardiovascular disease (CVD) prevalence specific to KAs is scarce. Furthermore, recent research suggests that there are considerable differences in CVD risk factors among KAs compared to non-Hispanic Whites (Shin et al, 2018). According to the 2011-2017 California Health Interview Survey (CHIS) with adults ages 18 years or older, one in four KA adults (24.3%) had high blood pressure (Adia et al, 2020).…”
mentioning
confidence: 99%
“…With regards to the multinomial regression analysis and ethnic differences in physical activity levels, Filipino Americans were more likely to be moderately to highly active compared to Koreans. In the few studies that disaggregated Asian Americans by groups, Korean Americans were generally less physically active compared to Filipinos [18,39]. A representative study of Asian Americans in California examining health risk behaviors among various Asian American groups found that among Koreans, 45% of men and 48% of women participated in moderate PA and 28% of men and 16% of women participated in vigorous PA, which was lower than Filipinos, where 52% of men and 56% of women participated in moderate PA and 30% of men and 26% of women participated in vigorous PA [39].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, or high blood pressure, is a common chronic disease reported in Filipinos and Korean Americans and frequently is associated with poor dietary and lifestyle factors, including physical inactivity and elevated stress [1,9,10,11,12,13]. Studies investigating hypertension prevalence in these groups found rates ranging from 48−67.5% in Filipinos and 30.8−53% in Koreans [8,14,15,16,17,18]. Hypertension prevention and management are important issues that require greater attention in these populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have found that this beneficial effect was not in direct proportion to the reduced risk of developing cardiovascular diseases (Ramsden et al, 2016;Ajmal et al, 2018;Trautwein et al, 2018;Górska-Warsewicz et al, 2019;Kouli et al, 2019). Salt content must also be mentioned as a further significant product attribute which is also known to contribute to the development of cardiovascular diseases (Mozaffarian et al, 2014;Farquhar et al, 2015;Shin et al, 2018;Frieden and Jaffe, 2018;Jayedi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%